The Relation between Self-confidence and Risk-taking among Female Students Living in Dormitories of Isfahan University of Medical Sciences - Reza Moradi; Mahan Mohammadi; Najmeh Bahman Ziari; Najmeh Teymourian (مجله ایرانی آموزش در علوم پزشکی, 2014)
Introduction: One of the main outcomes of self-esteem is self-confidence. Risk-taking is also a human characteristic influenced by self-confidence such that it is more likely for people with high self-confidence to make risky decisions with negative unpleasant consequences. Hence the present study aimed to investigate the relationship between self-confidence and risk-taking among female students living in dormitories of Isfahan University of Medical Sciences. Methods: In this descriptive-correlational study, 180 third year female students living in dormitories of Isfahan University of Medical Sciences were selected through Cochran formula and stratified sampling. Data collection tools were researcher-made questionnaires of self-confidence and risk-taking whose validity and reliability were verified. The collected data were analyzed using descriptive and inferential statistics tests (independent t test, ANOVA and Pearson Correlation coefficient test). Results: The level of self-confidence and risk-taking was moderate for the majority of respondents and there was a significant negative correlation between them (p = 0. 023 and r = - 0. 169). Scores of self-confidence and risk-taking did not differ significantly among married and single people and for different educational levels (p = 0. 714) but the mean scores of self-confidence (F=3. 138andP=0. 027) and risk-taking (F=3. 388 and P=0. 019) were significantly different among economic classes. Pearson correlation test also showed a significant negative correlation between self-confidence and risk-taking (P=0. 023 and r=-0. 169). Conclusion: According to inverse relationship between self-confidence and risk-taking in female students especially as to high-risk behaviors, it is suggested to take actions in order to increase their self-confidence such as social skill training, identifying potential talents and providing the conditions for their realization, proper use of their thoughts in decision making and improving their intellectual needs.